Application of the Sociodrama Method in History Learning for Class XI PH3 Students of SMKN 3 Jember in 2025-2026 - Muhidatul Qoriroh; Adzkiyak Adzkiyak; M. Iqbal Ibrahim Hamdani (FKIP - Universitas Riau, 2026)
History learning in schools is often dominated by conventional teaching methods that emphasize memorization, resulting in low student participation and limited meaningful learning experiences. This condition was also found in history learning for class XI PH3 students of SMKN 3 Jember, particularly on the topic of the Proclamation of Indonesian Independence. This study aims to describe the application of the sociodrama method in history learning, focusing on the learning process, student responses, and challenges encountered during its implementation. The research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews, questionnaires as supporting data, and documentation. The results show that the application of the sociodrama method creates a more active and interactive learning atmosphere, increases students’ participation, communication skills, motivation, and understanding of historical material. Students were able to comprehend historical events more meaningfully through role-playing activities. Despite challenges such as time constraints and varying levels of student confidence, these obstacles can be addressed through careful planning and teacher guidance. In conclusion, the sociodrama method is effective in improving the quality of history learning and can be used as an alternative instructional strategy in vocational high school contexts.